Schwannoma intraparenquimatoso con calcificación focal en lóbulo temporal - Targa G , Aylen Andrea; Martin , Clara; Gallardo, Federico; Díaz, Juan Francisco; Feldman , Santiago; Lambre, Jorge (Revista Argentina de Neurocirugía, 2021)
Intraparenchymal schwannomas have a very low incidence in the central nervous system. Currently, its true origin is not known, however, over the years, multiple theories have been described. This pathology mainly affects children and young adults. The main symptom is headache; and usually it is located in the supratentorial compartment. The Gold Standard is MRI where they usually present as hypointense lesions in T1, hyperintense in T2 that capture contrast in a homogeneous way. Once diagnosed, surgical resolution should be considered, since in most cases they represent a benign lesion, and their complete excision means resolution of the disease. The definitive diagnosis is obtained by pathological anatomy. We present a case of a 46-year-old patient with history of headache, its magnetic resonance revealed an extra axial lesion in the temporal lobe with considerable surrounding edema, the diagnosis was Intraparenchymal schwannoma with focal calcification in the temporal lobe.